The Role of Mothers in Maintaining Oral Health Towards Dental Hygiene - Yolanda Oktavia; Harsismanto J; Hendry Boy; Mira Sri Gumilar (JOSING: Journal of Nursing and Health, 2026)
The purpose of this study was to determine the relationship between mothers' roles in maintaining oral health and the dental hygiene of children at Melati Kindergarten and Mutiara Umi Kindergarten in Pematang Tiga District. This study was analytical with a cross-sectional approach. The population consisted of 35 children. The sample was taken using a total sampling technique, with 35 students. Data collection techniques included questionnaires and direct examination. Data analysis techniques used in this study were univariate and bivariate analysis using the Chi-square test. The results showed that mothers' roles in maintaining oral health were mostly in the poor category (74.3%). The dental hygiene of children at Melati Kindergarten and Mutiara Umi Kindergarten in Pematang Tiga District, as measured by the PHP-M index, was mostly in the moderate category (45.7%). In conclusion, there is a significant relationship between mothers' roles in maintaining oral health and the dental hygiene of children at Melati Kindergarten and Mutiara Umi Kindergarten in Pematang Tiga District, with an Asymp.sig value of 0.00 < 0.05.   Keywords: Mother's Role, Children Pretending, Dental Hygiene